The influence of secretin on ion transport in the human jejunum. Issue 6 (June 1973) - Hicks, T.; Turnberg, L. A.
Abstract : Using a triple-lumen tube perfusion technique in normal human subjects secretin (2U/kg/hour intravenously) was shown to reduce the absorption of sodium, potassium, and chloride in the most proximal 30 cm of jejunum but it had no effect on bicarbonate absorption. This effect was not due to an artefact produced by the entry of secretin-stimulated, bicarbonate-rich, pancreatic juice into the test segment. Absorption of sodium chloride and water was stimulated rather than inhibited by higher bicarbonate concentrations and the effect of secretin was obvious even when this factor was controlled by adjusting the bicarbonate concentrations of the test fluids. Secretin did not influence ion transport in the mid-jejunum. It is suggested that the effects described may indicate a physiological role for secretin in the intestine where it could prevent the too rapid dehydration of upper jejunal contents which might interfere with adequate mixing and digestion.